2014
DOI: 10.1159/000356314
|View full text |Cite
|
Sign up to set email alerts
|

Motility Abnormalities in Irritable Bowel Syndrome

Abstract: Background/Aims: The intestinal pathophysiology in irritable bowel syndrome (IBS) is largely unknown. The lactulose breath test has been used to identify small bowel bacterial overgrowth in these patients. Methods: We studied intestinal transit in patients with IBS using of the SmartPill® (SP) wireless pH/pressure recording capsule and performed lactulose breath tests to look for physiologic abnormalities. Results: A total of 35/46 (76%) of the IBS patients had prolonged gastric emptying times. Constipation-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 24 publications
0
27
0
3
Order By: Relevance
“…Alterations of intestinal microbiota have been directly linked to immunity, motility, and neurologic changes that are characteristic of IBS. Compared with conventionally raised mice, germ‐free mice exhibit delayed gastric emptying, slower intestinal transit times and are significantly more susceptible to enteric infections, manifestations that are also seen in IBS . Moreover, introduction of a single, typically commensal, intestinal bacterial species, such as Lactobacillus or Bifidobacterium, into a germ‐free mouse, results in prolonged intestinal transit times .…”
Section: Role Of Intestinal Microbiota In Ibs Pathogenesismentioning
confidence: 99%
“…Alterations of intestinal microbiota have been directly linked to immunity, motility, and neurologic changes that are characteristic of IBS. Compared with conventionally raised mice, germ‐free mice exhibit delayed gastric emptying, slower intestinal transit times and are significantly more susceptible to enteric infections, manifestations that are also seen in IBS . Moreover, introduction of a single, typically commensal, intestinal bacterial species, such as Lactobacillus or Bifidobacterium, into a germ‐free mouse, results in prolonged intestinal transit times .…”
Section: Role Of Intestinal Microbiota In Ibs Pathogenesismentioning
confidence: 99%
“…37 A more recent study revealed that IBS-C, which was associated with prolonged gut transit times, did not show an increase in positive testing for breath methane. 42 The authors explained the discrepancy with previous studies by variations in the definition of constipation, type of sugar, or proportion of patients with diarrhea. In contrast, measuring breath methane to determine therapeutic response to non-absorbable antibiotics such as neomycin and rifaximin has been well established.…”
Section: -mentioning
confidence: 81%
“…30 However, other studies argue that methane production is not restricted to constipation-predominant diseases. 37,41,42 In a study of 1372 subjects with functional GI disorders, including 212 IBS patients, diarrhea was more common than constipation in patients with high methane levels on LBT/fructose breath tests. Furthermore, two-thirds of IBS-C patients did not have elevated methane levels after either lactose or fructose.…”
Section: -mentioning
confidence: 99%
“…The pathogenesis of intestinal dysmotility is complex [32,33]. Many factors, such as inflammation, inhibitory agents, and neurogenic reflexes, are involved in the development and progression of intestinal dysmotility in various diseases [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%